Efektivitas Instrumen Penilaian Akreditasi terhadap Kinerja Sekolah - Lu Luatul Azizah; Nabila Az Zahra; Fira Lailatul Badri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Accreditation is the act of measuring the eligibility of education programs using a number of predetermined criteria. In its implementation, school accreditation uses instruments and criteria that are guided by the National Education Standards. This study aims to analyze the effectiveness of accreditation assessment instruments on improving school performance. The accreditation instrument, which is based on the National Education Standards, acts as a tool for evaluation to measure the quality and eligibility of schools in organizing education. This research uses a qualitative method with a normative approach and literature study. The results show that the accreditation instrument is effective in providing a comprehensive picture of school performance, ranging from aspects of learning, management, to facilities and infrastructure. This instrument assists in determining the school's strengths and weaknesses to guide the development of a sustainable improvement strategy. This study concludes that the accreditation assessment instrument is not only an assessment tool, but also a catalyst for the development of overall school performance.